2014
DOI: 10.1111/jam.12461
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase recombinantLactobacillus fermentumameliorates intestinal oxidative stress through inhibiting NF-κB activation in a trinitrobenzene sulphonic acid-induced colitis mouse model

Abstract: Aims: Superoxide dismutase (SOD) can prevent and cure inflammatory bowel diseases by decreasing the amount of reactive oxygen species. Unfortunately, short half-life of SOD in the gastrointestinal tract limited its application in the intestinal tract. This study aimed to investigate the treatment effects of recombinant SOD Lactobacillus fermentum in a colitis mouse model. Methods and Results: In this study, we expressed the sodA gene in Lact. fermentum I5007 to obtain the SOD recombinant strain. Then, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Modified SOD and propionyl-L-carnitine (PLC) have also been applied in clinical trials because of their strong treatment effects in IBD [201, 202]. Intravenous administration of a lecithinized human Cu/ZnSOD (PC-SOD) was found to suppress MPO and NF- κ B activity.…”
Section: New Therapies Targeting Oxidative Stress In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified SOD and propionyl-L-carnitine (PLC) have also been applied in clinical trials because of their strong treatment effects in IBD [201, 202]. Intravenous administration of a lecithinized human Cu/ZnSOD (PC-SOD) was found to suppress MPO and NF- κ B activity.…”
Section: New Therapies Targeting Oxidative Stress In Ibdmentioning
confidence: 99%
“…PC-SOD also exhibited benefits and safety when administered to UC patients for 14 days [203, 204]. In addition, a recombinant SOD (rec-SOD) elevated antioxidant activity and reduced ROS damage as well as MPO activity in the colon of a mouse colitis model [202]. PLC, an antioxidant molecule, can suppress ROS generation and remove free radicals leading to symptom relief in UC patients in phase II clinical trials [205, 206].…”
Section: New Therapies Targeting Oxidative Stress In Ibdmentioning
confidence: 99%
“…Then, the CAT and the GSHPx enzymes try to convert hydrogen peroxide to water to prevent the ROS injury in the cell. In the literature, a number of studies have shown a higher activity for the SOD and the CAT enzymes in TNBS colitis in rats [32][33][34][35]. On the contrary, Beno et al found the lower activities for the SOD and the CAT enzymes in colonic mucosa of 17 patients with idiopathic proctocolitis after 5-aminosalicylic acid treatment compared to activities of the same enzymes before the treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the studies performed by Watterlot et al (18) and LeBlanc et al (15), wild-type (WT) BL23 had only mild anti-inflammatory properties and did not induce marked IL-10 production in colon tissue, indicating that the amelioration effects on murine colon inflammation are limited. In 2014, Hou et al showed that oral administration of SOD-producing Lactobacillus fermentum I5007 (I5007) improved lipid peroxidation and immune parameters in the colon, thus ameliorating murine TNBS colitis (26). A partial, but significant, improvement effect was also observed with WT-I5007.…”
Section: Lactobacillusmentioning
confidence: 99%
“…lactis , as delivery agents have been attempted in recent years (Figure 1A). Many of these studies (1226) employ bacteria that have been termed “immunobiotics,” which have been defined as probiotic strains that are able to beneficially regulate mucosal immunity (27, 28). Immunobiotics are recognized by the pattern recognition receptors of epithelial and antigen-presenting cells such as dendritic cells and macrophages, and these immunobiotics are known to beneficially regulate innate and adoptive immune responses (Figure 1C); there have been tremendous advances in the clarification of strain-specific immune regulation functions at the cellular and molecular levels (28–32).…”
Section: Introductionmentioning
confidence: 99%